Social Security; A Public Policy for Good Governance in Nigeria: The Role of Nigerian Legislature - Eke-Jeffry, Emeh Ikechukwu (Journal of Social Economics Research, 2014)
The ability of any country to consistently improve her economic growth and development depends on good governance embedded in well-structured and diligently implemented public policies developed by officials within institutions of government to address public issues through the political process, called legislation. These officials, in Nigeria are the legislators, who are faced with the situation of jointly identifying a desirable future condition, creating policies and taking actions to move towards the desired future state; monitoring progress to allow for necessary adjustments; adjustments that will lead to that desired future state. That desired future state is the whole essence of governance. But in Nigeria today, especially since the upsurge of perennial and escalating unemployment, the lawmaking body of the nation cannot be said to have jointly identified the Nigerian problems, enacted policies that will ensure good governance in the country. Finding the reason for such inadequacies and the way forward is the thrust of this paper, as it x-rays the role of the Nigerian legislature in enacting social security policies for the unemployed and aged Nigerians for attainment of good governance where poverty, hunger, destitution and unemployment are eradicated.